2013
DOI: 10.1038/ncomms3155
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid high-speed atomic force–optical microscope for visualizing single membrane proteins on eukaryotic cells

Abstract: High-speed atomic force microscopy is a powerful tool for studying structure and dynamics of proteins. So far, however, high-speed atomic force microscopy was restricted to well-controlled molecular systems of purified proteins. Here we integrate an optical microscopy path into high-speed atomic force microscopy, allowing bright field and fluorescence microscopy, without loss of high-speed atomic force microscopy performance. This hybrid high-speed atomic force microscopy/optical microscopy setup allows positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…The resolution of the images on DOPS tubules was, however, insufficient to visualize the details of the helical reorganization process at the single-protein level, most probably because DOPS tubules have a low rigidity limiting HS-AFM resolution (13,20). To improve HS-AFM contouring and thus the resolution of the images, we opted for the use of rigid lipid nanorods formed by the spontaneous assembly of galactocerebrosides (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…The resolution of the images on DOPS tubules was, however, insufficient to visualize the details of the helical reorganization process at the single-protein level, most probably because DOPS tubules have a low rigidity limiting HS-AFM resolution (13,20). To improve HS-AFM contouring and thus the resolution of the images, we opted for the use of rigid lipid nanorods formed by the spontaneous assembly of galactocerebrosides (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…The use of fluorescence-related microscopy can help us to discern the detailed subcellular structures (e.g., cytoskeletons, cellular nuclei, cytoplasm) during the AFM indenting; thus, it greatly complemented the indentation by AFM. In addition, researchers have successfully combined high-speed AFM with fluorescence microscopy in the recent researches [82][83][84]. Suzuki et al [82] combined high-speed AFM with an optical fluorescence microscope by developing a tip-scanning system, and the results (observing the dynamics of living cells) showed that this system can remarkably improve the time resolution.…”
Section: Challenge and Outlookmentioning
confidence: 99%
“…Fukuda et al [83] have combined high-speed AFM with total internal reflection fluorescence microscopy, and this system can perform simultaneous topographic and fluorescence imaging at the single molecule level. Colom et al [84] have developed a hybrid high-speed atomic forceoptical microscope for visualizing single-membrane proteins on eukaryotic cells, allowing high-speed AFM imaging about 1,000 times faster than conventional AFM/ optical microscopy setups. The combination of high-speed AFM with fluorescence microscopy considerably accelerates the data acquisition rates of AFM, which is of evident significance in AFM nanoindentation.…”
Section: Challenge and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a combined system has already been developed. However, its purpose is not the simultaneous observation of HS-AFM/fluorescence images but the positioning of the cantilever tip on a region of interest within a large object (e.g., eukaryotic cells) visualized with fluorescence microscopy (Colom et al 2013;Shibata et al 2015). In this hybrid system, the sample stage is scanned, and therefore the fluorescence image oscillates during HS-AFM imaging.…”
Section: Hybrid Hs-afm/optical Microscopy Systemmentioning
confidence: 99%